Modelling and pressure control of the expiratory cycle for mechanical ventilation systems. (January 2022) - García-Violini, Demián; Faedo, Nicolás; Cafiero, Eduardo
Abstract: This study addresses the pressure control design of the expiratory cycle for mechanical ventilation systems. In particular, the study presented herein can be separated into two main stages: accurate system modelling, and suitable control design. Firstly, using generic modelling assumptions for pneumatic systems, the expiration dynamical model is presented and analysed. Secondly, a pressure tracking controller design, inspired by 'traditional' control structures, is proposed, considering both pressure and flow compensation combined with a gain-scheduling structure. Experimental results are presented throughout this study, both for modelling validation and controller implementation, using a commercial mechanical ventilation system. Such results show that the presented control strategy thoroughly verifies the specifications required by standard respiratory therapies, considering a broad range of patients features, in an extended dynamic range.